AN ANALYSIS OF HUMAN VALUES OF THE MAIN CHARACTERS OFTHE BOOK OF LOVE MOVIE - Rezi Dwita; Hazairin Eko Prasetyo (JELLT (Journal of English Language and Language Teaching), 2018)
The objectives of this study are: (1) to describe the main characters of The Book of Love, (2) to describe the human values of the main characters of The Book of Love. In this study the writer used descriptive and qualitative techniques. The writer collected the data through observation of the movie by watching and reading the script of the movie several times to get information about the characters and the human values. Then, the writer collected the data and analyzed them. In analyzing the data, the writer used coding, decoding, categorization, and confirmation. The analysis focused on the characters and the human values in The Book of Love movie. The results of the researchshow that there are three main characters of The Book of Love movie; they are Henry, Millie, and Penny.Besides, there are seven human values that the writer found in the movie. Those values are self-direction, stimulation, achievement, security, conformity, tradition,Â  and benevolence. The seven values have good influence in real life. Thedominant values presented in this movie are benevolance (helpful) and self-direction (curiousity and creativity).